The Influence of the Project Based Learning Model in the Edu Entrepreneur Course on Student Creativity - Fitri Aisyah; Ranti Firdaus; Afrina Refdianti (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The primary aim of this study is to determine the influence of the Project Based Learning (PjBL) model on the creativity of Arabic Language Education students. It specifically evaluates how implementing practical projects in the Edu Entrepreneur course stimulates innovative thinking and aligns with higher education performance standards. Methodology: This research utilizes a quantitative approach with a Pre-Experimental One-Group Pretest-Posttest Design. Data were collected from 23 students selected through purposive sampling. Instruments include the Creative Thinking Scale (CTS) and observation sheets for product assessment. Analysis was performed using SPSS software, applying descriptive statistics and Paired Sample T-Tests. Main Findings: The findings reveal a significant increase in creativity scores, rising from a pre-test mean of 72.71 to a post-test mean of 88.50, reaching the